Observations of the extreme runaway HD271791: Nucleosynthesis in a core-collapse supernova - Schaffenroth, Veronika; Przybilla, Norbert; Butler, Keith; Irrgang, Andreas; Heber, Ulrich (Proceedings of Science, 2014)
Some young, massive stars can be found in the Galactic halo. As star formation is unlikely to occur in the halo, they must have been formed in the disk and been ejected shortly afterwards. One explanation is a supernova in a tight binary system. The companion is ejected and becomes a runaway star. HD271791 is the kinematically most extreme runaway star known (Galactic restframe velocity 725±195km s-1, which is even larger than the Galactic escape velocity). Moreover, an analysis of the optical spectrum showed an enhancement of the α-process elements. This indicates the capture of supernova ejecta, and therefore an origin in a core-collapse supernova. As such high space velocities are not reached by the runaway stars in classical binary supernova ejection scenarios, a very massive but compact primary, probably of Wolf-Rayet type is required. HD271791 is therefore a perfect candidate for studying nucleosynthesis in a supernova of probably type Ibc. The goal of this project is to determine the abundances of a large number of elements from the α-process, the iron group, and heavier elements by a quantitative analysis of the optical and UV spectral range. Detailed line-formation calculations are employed that account for deviations from local thermodynamic equilibrium (non-LTE). We intend to verify whether corecollapse supernova are a site of r-process element production. Here, we state the current status of the project.
CRIS-Team Scopus Importer:2020-12-21